Sorption Study of Se(-II) onto Illite, Bentonite, and Shale Under High Ionic Strength Conditions - Walker, Andrew (My University, 2018)
Due to the very long half-life of Se-79 and its presence in used nuclear fuel, Se is an element of interest in the safety assessment for a deep geological repository (DGR) for used nuclear fuel. Sorption of radionuclides onto the surrounding host rocks and engineered barrier materials is a potential retardation mechanism for radionuclide transport. This thesis investigates the sorption of Se(-II) onto illite, bentonite (engineered barrier material), and shale under high ionic strength conditions relevant to a Canadian DGR. The ionic strength and pH dependence of Se(-II) sorption onto illite, bentonite, and shale were studied. A non-electrostatic surface complexation model was also developed for Se(-II) sorption onto illite and montmorillonite to investigate the sorption mechanisms by which Se(-II) sorbs onto these solids.
Keywords: selenium; reducing condition; sorption; distribution coefficient; anion; surface complex